Investigation of kinetics leaching and extraction of vanadiumpentoxyde as a function of temperature - Nacevski, Nikola (Kovine zlitine tehnologije, 1997)
In several thermal power plants in operation in the Republic of Macedonia a substantial quantity of ash is produced by oil burning. Ashes are considered as highly hazardous for the environment due to their fine particle size. On the other hand, analyses carried our so far, indicate appreciable contents of vanadium, gallium, berillium etc. in the ashes.
Keywords: olja; pepel; vanadij; kemijska kinetika; luženje